Surgical repair of post-traumatic finger contracture in a child - SK Sekendar Ali; Narendra Nath Mukhopadhyay; Partha Bhar; Niloy Narayan Sarkar (Elsevier, 2022)
Background: To present the experience of management of the digital flexion contractures. Case presentation: We present a case of 5 yrs old boy child, Patient with post-traumatic contracture of Ring finger of left hand last 3 months. Multiple continuous Z-plasty performed to correct deformity. Conclusions: Careful assessment and early prompt correction results in return of normal hand function. Early treatment of contractures with Z-plasty results in the improvement of finger mobility.